MSME’s Financing Decisions and the Roles of Financial Literacy and Microbusiness Demographics - Mutasowifin, Ali; Sutisna, Cindy (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, contributing 60.5% to the GDP, employing 96.9% of the workforce, and accounting for 15.69% of exports. However, MSMEs still face capital problems. Many of them struggle to access financial institutions due to their limited financial literacy. This research aims to identify the level of financial literacy among microbusinesses. The survey involved 60 respondents in the Cibinong District of Bogor Regency and analyzed how financial literacy levels and demographic factors influence microbusinesses’ decisions regarding the use of financing products from micro financial institutions (MFIs). The analytical method employed in this study is logistic regression. The research results indicate that financial attitudes, education, and income have a significant positive impact on financing decision from micro financial institutions, while financial knowledge and behavior have a significant negative impact. Keywords: MSME, MFI, financial literacy, demography, micro businesses ABSTRAK Usaha Mikro, Kecil dan Menengah (UMKM) memiliki peran penting dalam perekonomian Indonesia dengan kontribusi terhadap PDB 60,5%, penyerapan tenaga kerja 96,9%, dan ekspor 15,69%. Namun, UMKM masih menghadapi masalah permodalan. Banyak UMKM masih belum mampu mengakses lembaga keuangan karena literasi keuangannya yang rendah. Penelitian ini bertujuan mengidentifikasi tingkat literasi keuangan usaha mikro, dengan menyebarkan kuesioner kepada 60 responden di Kecamatan Cibinong, Kabupaten Bogor dan menganalisis pengaruh tingkat literasi serta faktor demografi terhadap keputusan usaha mikro dalam menggunakan produk pembiayaan di lembaga keuangan mikro (LKM). Metode analisis yang digunakan adalah regresi logistik. Hasil penelitian menunjukkan bahwa sikap keuangan, pendidikan, dan pendapatan berpengaruh signifikan positif terhadap pengambilan keputusan menggunakan produk pembiayaan lembaga keuangan mikro, sementara pengetahuan dan perilaku keuangan berpengaruh signifikan negatif. Kata kunci: UMKM, LKM, literasi keuangan, demografi, bisnis mikro